2020
DOI: 10.1177/0894318420965219
|View full text |Cite
|
Sign up to set email alerts
|

Neuman Systems Model With Nurse-Led Interprofessional Collaborative Practice

Abstract: The Neuman Systems Model was developed to create a structure to depict nursing clients as complex systems, in constant energy exchange with their environments, comprised of multiple interrelated parts. It has been widely used in practice, education, research, and administration. An analysis of the theory, based upon Meleis’ methods, was conducted. The theory has high utility and a large circle of contagiousness despite its complexity, lack of teleology, and level of abstractness. Based upon this analysis, a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Ahmadii et al, (2021) similarly reported a reduction in tension and anxiety among mothers of hospitalized children using the Betty Neuman's model [10]. A study by Montano (2021) aligns with these findings, highlighting the model's role in stress reduction and enhanced adaptation among patients by fostering an understanding of stress [14].…”
Section: │ Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Ahmadii et al, (2021) similarly reported a reduction in tension and anxiety among mothers of hospitalized children using the Betty Neuman's model [10]. A study by Montano (2021) aligns with these findings, highlighting the model's role in stress reduction and enhanced adaptation among patients by fostering an understanding of stress [14].…”
Section: │ Discussionmentioning
confidence: 66%
“…Collectively, these studies underscore the practical utility of Betty Neuman's systemic model in nursing care, particularly in its systemic paradigm that emphasizes interprofessional collaboration and stress prevention through the identification and planning of stressful factors [14]. The model's foundation in prevention principles, interpersonal communication, and understanding the diverse dimensions of patients contributes to its effectiveness in addressing their needs [10,25,26].…”
Section: │ Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because the nature of the data collected had revealed the existence of difficulties (stressors) and response patterns (reconstitution strategies), the research team developed a secondary analysis guided by the NSM. The Consolidated Criteria for Reporting Qualitative studies (COREQ) guidelines were followed [25].…”
Section: Methodsmentioning
confidence: 99%
“…Sengun (2016) showed that Neuman's model reduced stress and increased the quality of care for cancer patients (17). Montano (2021) reported that the implementation of this care model increased clinical performance in nursing (18) because the philosophy of this model is based on identifying and preventing stressors (19). The use of nursing models and theories can increase the quality of clinical care and reduce treatment costs (13).…”
Section: Introductionmentioning
confidence: 99%